A pseudo-ketogenic sugar-ghee-enriched diet induces metabolic and immune alterations in rats: a model of flawed ketogenic diet practice - Ismail, Farah; Khalifeh, Mohammad; Hananeh, Wael; Khataybeh, Batool; Al-Azaizeh, Rasha; Al-Ghadi, Muath Q. (Frontiers in Veterinary Science, 2025)
IntroductionThe ketogenic diet (KD) has gained popularity due to its reported benefits on weight loss and metabolic health. However, in real-world settings, KD is frequently misapplied individuals often continue consuming sugar or fail to calculate macronutrient ratios accurately. These flawed patterns may still result in weight loss but carry unclear long-term effects on metabolism and immune function.MethodsThe present study aimed to simulate one such misapplication by developing a sugar-ghee-enriched diet (SGED) for Wistar male rats, rich in animal-derived fat and added sugar. The diet provided approximately 31.7% of energy from fat with a ketogenic ratio of 0.21:1, well below the threshold for nutritional ketosis. Rats were divided into control and SGED groups and fed their respective diets for 33 days. We examined parameters including body weight, visceral fat deposition, serum lipid levels, selected cytokines (IL-6, TNF-α, IL-10, TGF-β), and performed histological examinations of the liver, kidney, and intestinal tissues.ResultsSGED-fed rats showed a reduction in total body weight but exhibited a significant increase in visceral fat deposition and a dyslipidemic profile, marked by elevated serum triglyceride, cholesterol, vLDL levels, and atherogenic index. Immune modulation was also observed, with increased levels of TNF-α, IL-10, and TGF-β, and a decrease in IL-6. No major histopathological changes were found in the examined organs.DiscussionTo our knowledge, this is the first study to introduce an experimental rat model representing pseudo-ketogenic dietary (PKD) behavior, characterized by high animal fat intake combined with added sugar, leading to superficial weight loss without achieving ketogenic thresholds. The SGED model reveals potential risks for adverse immune and metabolic outcomes, emphasizing the need to address flawed interpretations of ketogenic dieting.